Metal-organic frameworks for diagnosis and therapy of infectious diseases - Quijia, Christian Rafael [UNESP]; Alves, Renata Carolina [UNESP]; Hanck-Silva, Gilmar [UNESP]; Galvão Frem, Regina Célia [UNESP]; Arroyos, Guilherme [UNESP]; Chorilli, Marlus [UNESP] (Taylor & Francis, 2022)
Infectious diseases are one of the leading cause of mortality and morbidity worldwide. Metal-Organic Frameworks (MOFs), which are porous coordination materials composed of bridging organic ligands and metallic ions or clusters, exhibits great potential to be used against several pathogens, such as bacteria, viruses, fungi and protozoa. MOFs can show sustained release capability, high surface area, adjustable pore size and structural flexibility, which makes them good candidates for new therapeutic systems. This review provides a detailed summary of the biological application of MOFs, focussing on diagnosis and treatment of infectious diseases. MOFs have been reported for usage as antimicrobial agents, drug delivery systems, therapeutic composites, nanozymes and phototherapies. Furthermore, different MOF-based biosensors have also been developed to detect specific pathogens by electrochemical, fluorometric and colorimetric assays. Finally, we present limitations and perspectives in this field.
Keywords: antimicrobial agents; biosensors; drug delivery systems; MOFs; phototherapies; therapeutics